2007
DOI: 10.1089/jmf.2006.078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elm Bark (Ulmus davidianavar.japonica) Extracts on the Modulation of Immunocompetence in Mice

Abstract: The immunomodulative effects of elm bark extract were studied in vitro by the proliferation of splenocytes and the production capacity of three kinds of cytokines [interleukin (IL)-1beta, IL-6, and tumor necrosis factor (TNF)-alpha] by mouse peritoneal macrophages cultured with various fractions (methanol, hexane, chloroform, ethyl acetate, butanol, and water) of elm bark extract. Splenocyte proliferation and cell viability of peritoneal macrophages were increased with concentrations of polar fractions, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In particular, Ulmus davidiana var. japonica (elm bark) extracts are known to increase immunocompetence, that is, to enhance splenocyte proliferation and cytokine production capacity by activated macrophages in mice [ 13 ]. In one study, it was shown that Ulmus davidiana var.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Ulmus davidiana var. japonica (elm bark) extracts are known to increase immunocompetence, that is, to enhance splenocyte proliferation and cytokine production capacity by activated macrophages in mice [ 13 ]. In one study, it was shown that Ulmus davidiana var.…”
Section: Discussionmentioning
confidence: 99%
“…japonica. 44 Recently, many more starch-like polysaccharides have been found to modulate the immune system and have antitumor activity. 33,34 The activity might be caused and influenced by some fine structures such as glycosidic linkages, the length of the backbones, the length of side chains, the number of branched points, and the molecular size.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 In addition, extracts from this plant inhibited angiogenesis, boosted immunocompetence, and reduced inflammation. [7][8][9] The present study reports the isolation of an antiinflammatory agent (Compound 1) from U. davidiana var. japonica.…”
Section: Introductionmentioning
confidence: 82%